Perceptions of University Students on Entrepreneurship; A South African Case Study - Harris Maduku; Makhosazana Faith Vezi-Magigaba (Journal of Economics and Behavioral Studies, 2019)
South Africa currently suffers from high levels of poverty, inequality and unemployment. However, the involvement of citizens in entrepreneurship is still very low for the country to rely on entrepreneurship as a solution to curb its socio-economic crisis. Survival rates of established businesses have also proved to be worrisome in the country with lack of skills cited as one of the most contributing factors. The country is in need of more entrepreneurs with better skills and understanding of business as that can facilitate job creation, poverty alleviation and economic growth. The objective of this paper is to analyse how University students perceive entrepreneurship in South Africa. Using random sampling, the study used a structured questionnaire to gather data from University of Zululand students. Employing the probit logistic regression technique on 152 observations, the study finds Age, family business background, business course and entrepreneurial interest statistically significant on influencing perceptions of students towards entrepreneurship. The study recommends that the South African Universities’ curricular be revised so as to start equipping all registered students with entrepreneurship skills as this impact on their perceptions to starting their own businesses after graduation. Also Universities should start acting as innovation and entrepreneurial hubs for both their students and the business community.